Autoexamen mamario para prevención del cáncer de mama en estudiantes de Enfermería de la Universidad Nacional de Loja - Cueva Yaguana, Carmen Elizabeth (2022)
Breast cancer is a more common cancer in women, it is currently a public health problem, because every year increases its incidence rate. Therefore, the objective of this research was to analyze the knowledge and practice about breast self-examination in nursing students of the Universidad Nacional de Loja in order to design edu-communicational actions of prevention of breast cancer. The present study was based on a descriptive-quantitative cross-sectional study in which 114 nursing students were surveyed. The information was collected using an instrument called "Breast cancer knowledge and breast self-exam practice in middle-aged women", with a reliability of 0.917. The results obtained showed that: 40% know the definition of breast self- examination, 90% know its importance and 94% to whom it is addressed, regarding the initiation of breast self-examination, more than 50% indicates that it should be performed from the age of 20, frequently every month, however, 60% are unaware of the concept and position in which this review should be conducted. Concerning the practice, more than 50% of students do not do it because they do not know how to do it and consider it indifferent, while a low percentage of students say they do it by personal decision, highlighting that only 11% do it correctly, examining both breasts both standing and lying down. Concluding that about 50% of the students of the Nursing Career have enough knowledge, however, the practices are not the most suitable